Iramuteq em um acervo literário: amostra de um trabalho possível - Krug, Flavia Susana (2017)
The purpose of this Master's dissertation research is to explore computer software designed for extensive and accurate textual analysis: the IRAMUTEQ Software. From this experience in a literary collection, we intend to provide more details about the use and performance of the chosen program. The type of experience report was made from the qualitative descriptive analysis of the resulting corpora data prepared according to the IRAMUTEQ Software Installation Manual. Each corpora consisted of journalistic chronicles written by the journalist and writer Josué Guimarães, under the pseudonyms Dom Camilo and Peppone for the newspapers Folha da Tarde and Hoje, respectively, in 1954. The corpora were submitted to individual analysis by the software and only after The data obtained from the Similitude Analysis and Word Cloud resources provided by the IRAMUTEQ Software were analyzed together to identify peculiarities, similarities, convergences and divergences between pseudonyms, language, common and differentiated expressions, among other characteristics that are relevant for observation and notes. The discussion of the data occurred taking into account the function of the words attributed in the text, in their context, used by the author of the journalistic chronicles to portray the social-political-educational context of that period of Brazilian society, as well as the level of prominence suggested by the software. The dissertation was theoretically based on well-known names such as Roberto Acízelo de Souza (2007), in his work Theory of Literature, that deals with the art of eloquence, good argument, word, rhetoric; Alberto Cupani (2011), in Philosophy of Technology: an invitation, when it provides us with an existential philosophical debate about the plurality and complexity of the philosophical problems bound up with technology and Lúcia Santaella (2013), which deals with expanded literature, Objects of communication and information acquired its space in the era of hypermobility. In this sense, it will be possible to contribute, dynamically, from this research to a greater dissemination of IRAMUTEQ Software in literary studies, including, enriching and understanding, even more, the journalistic-literary universe left by Josué Guimarães.